ANALISIS FAKTOR PENGHAMBAT PEMANFAATAN RUANG MENYUSUI DI TEMPAT KERJA PADA PEKERJA WANITA DI PT. DAYA MANUNGGAL (Unnes Journal of Public Health, 2016)
Abstrak Berdasarkan data jumlah ibu menyusui di PT. Daya Manunggal hanya 22,6% saja yang menggunakan ruang menyusui.Tujuan penelitian ini untuk menganalisis faktor penghambat pemanfaatan ruang menyusui di tempat kerja pada pekerja wanita di PT. Daya Manunggal. Jenis penelitian ini adalah penelitian explanatory research, dan rancangan penelitiannya adalah cross sectional. Populasi dalam penelitian ini pekerja wanita menyusui di PT. Daya Manunggal berjumlah 84 orang. Sampel berjumlah 33 pekerja wanita menyusui. Teknik pengambilan sampel dengan teknik Random Sampling. Instrumen yang digunakan dalam penelitian ini adalah kuesioner. Analisis datayang digunakan adalah analisis univariat dan bivariat dengan menggunakan uji Chi Square dengan derajat kemaknaan (a) = 0,05. Hasil Penelitian dan pembahasan, menunjukan ada hubungan antara dukungan keluarga (p=0,042) dan dukungan atasan kerja (p=0,042) dengan pemanfaatan ruang menyusui di PT. Daya Manunggal. Tidak ada hubungan antara tingkat pendidikan (p=0,212), pengetahuan (p=0,521), kondisi kesehatan (p=0,343), kebijakan perusahaan (p=0,448), ketersediaan fasilitas (p=0,351), dukungan petugas kesehatan di tempat kerja (p=0,675), dukungan rekan kerja (p=0,479) dengan pemanfaatan ruang menyusui di PT.Daya Manunggal Abstract Based on data of the number female workers which being on breastfeed at PT. Daya Manunggal only 22.6% are using breastfeeding room. The aim of this study is to analyze the inhibiting factor of breastfeeding room utilization usage of female workers at PT. Daya Manunggal.This type of research explanatory research, with cross sectional study design. The population in this study were female workers whose being on breastfeed at PT. Daya Manunggal which amount to 84 worker. The number of sample are 33 female workers. The technique which used in this research was Random Sampling. Instruments used in this study was a questionnaire. Data analysis performed using univariate and bivariate Chi Square test with degrees of significance of 0,05. The result of the research and the discussion show that there is correlation between family support (p = 0.042) and supervisor support (p = 0.042) with the usage of breastfeeding room at PT. Daya Manunggal. There is no relationship between the level of education (p = 0.212), knowledge (p = 0.521), health conditions (p = 0.343), company policies (p = 0.448), the availability of facilities (p = 0.351), support health officer in the workplace (p = 0.675), support co-workers (p = 0.479) with the usage of breastfeeding room at PT.Daya Manungga. Suggestions can be submitted to female workers which being on breastfeed is to improve self-motivated to utilize the breastfeeding room in the workplace in order to support exclusive breastfeeding program. For the Company appealed to the supervisor in each of department to give better support of exclusive breastfeeding programs such as giving a special time to squeeze breast milk so they can utiliz breastfeed room in the workplace. For families provide support and motivation in order to willing to give exclusive so they got motivated to utilize the breastfeeding room in the workplace.